Comparative Immature Morphology of Brazilian Fire Ants (Hymenoptera: Formicidae: Solenopsis) - Eduardo Gonçalves Paterson Fox; Daniel Russ Solis; Mônica Lanzoni Rossi; Jacques Hubert Charles Delabie; Rodrigo Fernando de Souza; Odair Correa Bueno (Psyche: A Journal of Entomology)
Although common in Brazil, the biology of the fire ant Solenopsis saevissima (Smith) is still poorly studied. Larval descriptions are useful to genus-level ant systematics and sometimes to species-level taxonomy. This study presents a detailed description of juveniles of S. saevissima from Brazil, which were compared with Brazilian specimens of Solenopsis invicta Buren, Solenopsis geminata (Fabricius), and Solenopsis altipunctata Pitts. Different larval instars were separated by diagnostic morphological traits which were confirmed by observing moults. Reproductive larvae could be easily sorted by their distinctive body dimensions and shape. Contrary to previous reports on this species, the larvae of S. saevissima proved to be generally identical to those of S. invicta, while a few specimens resembled those of other close species, such as Solenopsis megergates Trager. Mature larvae thus presented considerable intraspecific variation in some characters recently proposed to aid fire ant species separation (morphology of head hairs).